In‐hospital stroke after transcatheter aortic valve implantation: A UK observational cohort analysis. Issue 4 (11th August 2020) - Myat, Aung; Buckner, Luke; Mouy, Florence; Cockburn, James; Baumbach, Andreas; Banning, Adrian P.; Blackman, Daniel J.; Curzen, Nick; MacCarthy, Philip; Mullen, Michael; de Belder, Mark; Cox, Ian; et al.
Abstract: Objectives: We sought to identify baseline demographics and procedural factors that might independently predict in‐hospital stroke following transcatheter aortic valve implantation (TAVI). Background: Stroke is a recognized, albeit infrequent, complication of TAVI. Established predictors of procedure‐related in‐hospital stroke; however, remain poorly defined. Methods: We conducted an observational cohort analysis of the multicenter UK TAVI registry. The primary outcome measure was the incidence of in‐hospital stroke. Results: A total of 8, 652 TAVI procedures were performed from 2007 to 2015. There were 205 in‐hospital strokes reported by participating centers equivalent to an overall stroke incidence of 2.4%. Univariate analysis showed that the implantation of balloon‐expandable valves caused significantly fewer strokes (balloon‐expandable 96/4, 613 [2.08%] vs. self‐expandable 95/3, 272 [2.90%]; p = .020). After multivariable analysis, prior cerebrovascular disease (CVD) (odds ratio [OR] 1.51, 95% confidence interval [CI 1.05–2.17]; p = .03), advanced age at time of operation (OR 1.02 [0.10–1.04]; p = .05), bailout coronary stenting (OR 5.94 [2.03–17.39]; p = .008), and earlier year of procedure (OR 0.93 [0.87–1.00]; p = .04) were associated with an increased in‐hospital stroke risk. There was a reduced stroke risk in those who had prior cardiac surgery (OR 0.62 [0.41–0.93]; p = .01) and a first‐generation balloon‐expandable valve implanted (OR 0.72 [0.53–0.97]; p = .03). In‐hospital stroke significantly increased 30‐day (OR 5.22 [3.49–7.81]; p < .001) and 1‐year mortality (OR 3.21 [2.15–4.78]; p < .001). Conclusions: In‐hospital stroke after TAVI is associated with substantially increased early and late mortality. Factors independently associated with in‐hospital stroke were previous CVD, advanced age, no prior cardiac surgery, and deployment of a predominantly first‐generation self‐expandable transcatheter heart valve.